A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan - Kosterin, Oleg E.; Akimbekova, Nazymgul; Dubatolov, Vladimir V.; Sivec, Ignac (Zootaxa, 2017)
Taeniopteryx araneoides Klápalek, 1902, a stonefly species with brachypterous males, known historically from the Danube, Elbe, and Dniester rivers, but considered to be extinct at least in Europe for more than a century. This species has also been doubtfully reported from Krasnoyarsk, Central Siberia. However, we report this species to be still thriving in the Irtysh River at the cities of Omsk (West Siberia, Russia) and Pavlodar (North Kazakhstan). The occurrence of this species reported least fifty years ago from the Yenisey River at Krasnoyarsk, Russia is considered possible. Unlike the widespread Palaearctic T. nebulosa (Linnaeus, 1758) that occurs in a broad range of stream types, T. araneoides is a potomon species, apparently confined to large rivers. In this habitat, it appears vulnerable to anthropogenic impacts and may be unable to compete with T. nebulosa. The construction of dams and reservoirs has apparently extirpated T. araneoides from most of its former geographical range.